Impairment of aversive episodic memories during COVID-19 Pandemic: The impact of emotional context on memory processes - León, Candela Sofía (2021)
The threatening context of the COVID-19 pandemic provided a unique settingto study the effects of negative psychological symptoms on memory processes. Episodic memory is an essential function of the human being related to the ability tostore and remember experiences and anticipate possible events in the future.Studying this function in this context is crucial to help understand what effects thepandemic will have on the formation of episodic memories. To study this, theformation of episodic memories was evaluated by free recall, recognition, andepisode order tasks for an aversive and neutral content. The results indicated thataversive episodic memory is impaired both in the free recall task and in therecognition task. Even the beneficial effect that emotional memory usually has for theepisodic order was undermined as there were no differences between the neutraland aversive condition. The present work adds to the evidence that indicates that thelevel of activation does not modify memory processes in a linear way, which also depends on the type of evocation that people are asked and the characteristics ofthe content to be encoded.